Finding the optimal solution in pharmaceutical technological research using statistical methods with quantitative factors - Kutova, Olga; Sahaidak-Nikitiuk, Rita; Kovalevska, Inna; Demchenko, Nataliya (ScienceRise: Pharmaceutical Science, 2024)
The aim. Developing a methodological approach to determining the optimal solution using statistical methods in pharmaceutical and technological research with quantitative factors on the example of establishing the optimal content of filler in a solid dispersion in the manufacture of granules. Materials and methods. The methodology for finding an optimal solution is shown in the example of the development of granules containing a solid dispersion of quercetin with polyethylene oxide 6000. To determine the optimal amount of filler, the method of mathematical modelling was applied using statistical analysis and multiple criterion optimization. Software tools such as MS Excel and Mathcad 14 spreadsheets were used to process the experimental data and perform calculations. Results. The problem is formalized in a form suitable for solving by experimental and statistical methods. The issues of constructing mathematical models in the form of regression equations characterizing the effect of the quantitative content of the filler on several pharmacy-technological parameters of granules based on experimental data are considered. Attention is focused on the peculiarities of using static methods for processing experimental data in pharmaceutical research, namely, on establishing the structure of regression equations and assessing their adequacy. The criterion of multi-criteria optimization is proposed, which is formed based on the obtained regression equations, considering the restrictions imposed on each individual criterion. Conclusions. A methodological approach to determining the optimal solution in pharmaceutical technological research with quantitative factors using experimental and statistical methods and the theory of multi-criteria optimization has been tested on the example of determining the optimal content of filler in a solid dispersion in the manufacture of granules. The optimal ratio of filler to solid dispersion was determined, which ensures the maximum approximation of all studied pharmacy-technological parameters of granules to their optimal values. None of the indicators exceeds the limits set by the researcher and has the minimum possible deterioration relative to the individually determined optimum